2016
DOI: 10.1111/jcmm.12793
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of lymphatic endothelial precursor cells and lymphatic neovascularization in primary Sjögren's syndrome

Abstract: Although lymphatic neovascularization may be a key feature of chronic inflammation, it is almost unexplored in primary Sjögren's syndrome (pSS). A recent study revealed a pro‐lymphangiogenic function of interleukin (IL)‐17, a leading player in pSS pathogenesis. The aims of the study were to investigate lymphangiogenic mediators and lymphatic vasculature in pSS, as well as their possible association with IL‐17. Circulating lymphatic endothelial precursor cells (LEPCs) and Th17 cells were enumerated in pSS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Lymphocytic infiltration in exocrine glands is the most important histological characteristic of patients with pSS. Previous studies have shown that IL‐17 is mainly expressed in the periductal and perivascular infiltrates of the salivary glands, with the level of expression correlated with the severity of glandular inflammation . However, among the 7 studies reporting IL‐17 expression under conditions of weak and strong lymphocytic infiltration, no significant overexpression of IL‐17 in severe inflammatory patients is found.…”
Section: Discussionmentioning
confidence: 92%
“…Lymphocytic infiltration in exocrine glands is the most important histological characteristic of patients with pSS. Previous studies have shown that IL‐17 is mainly expressed in the periductal and perivascular infiltrates of the salivary glands, with the level of expression correlated with the severity of glandular inflammation . However, among the 7 studies reporting IL‐17 expression under conditions of weak and strong lymphocytic infiltration, no significant overexpression of IL‐17 in severe inflammatory patients is found.…”
Section: Discussionmentioning
confidence: 92%
“…Apoptotic death of ECs has been described by three different mechanisms [ 9 15 ]. First, ECs may be intrinsically activated and die due to membrane folding through autocrine Fas/FasL interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to exocrine cells accompanies lymphocyte infiltrates of ductal epithelial cells (ECs), which results in oral and ocular dryness [ 9 15 ]. However, these aggregates evolve from mild to focal, focal to diffuse, and vary in composition according to the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…On their surface, LEPC display CD34 and CD133, likewise their blood vascular counterpart (ie, EPC), but they present vascular endothelial growth factor receptor (VEGFR)-3 (also called Flt4) instead of VEGFR-2 6. Interestingly, an expansion of circulating LEPC has been recently shown in rheumatic diseases such as spondyloarthritis and primary Sjögren’s syndrome 7 8. As far as SSc is concerned, heterogeneous data have been reported on the numbers and functions of EPC,2 but no data are currently available on LEPC.…”
mentioning
confidence: 99%